2022
DOI: 10.3390/diagnostics12102469
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic and Therapeutic Role of Circular RNA HIPK3 in Human Diseases

Abstract: Circular RNAs (circRNAs) are a class of noncoding RNAs with closed-loop of single-stranded RNA structure. Although most of the circRNAs do not directly encode proteins, emerging evidence suggests that circRNAs play a pivotal and complex role in multiple biological processes by regulating gene expression. As one of the most popular circRNAs, circular homeodomain-interacting protein kinase 3 (circHIPK3) has frequently gained the interest of researchers in recent years. Accumulating studies have demonstrated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated that circRNAs act as microRNA sponges to regulate downstream target gene expression in tumour development 35–37 . We used the Circular RNA Interactome (CircInteractome, https://circinteractome.irp.nia.nih.gov/) to identify potential target microRNAs for circTEX2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that circRNAs act as microRNA sponges to regulate downstream target gene expression in tumour development 35–37 . We used the Circular RNA Interactome (CircInteractome, https://circinteractome.irp.nia.nih.gov/) to identify potential target microRNAs for circTEX2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that circRNAs act as microRNA sponges to regulate downstream target gene expression in tumour development. 35 , 36 , 37 We used the Circular RNA Interactome (CircInteractome, https://circinteractome.irp.nia.nih.gov/ ) to identify potential target microRNAs for circTEX2. We selected 10 candidate microRNAs based on the results of our prediction and previous studies and performed qRT‐PCR to detect their expression of AGS and MKN45 co‐cultured with M2 macrophages NC or si‐circTEX2‐derived exosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, one circRNA can adsorb several miRNAs, one miRNA molecule can target a wide range of different mRNAs with the involvement of corresponding protein products in the development of several pathologies, and individual circRNAs can be markers of several diseases simultaneously. Many circRNAs, in particular circMTO1, circHIPK3, сirc_0001946, circPTPRA, and circCOL1A1, are potential targets for therapy or biomarkers of CAD ( Table 1 and Table 2 ), and play critical roles in cancer progression as well [ 175 , 176 , 177 , 178 , 179 ]. Additional comprehensive studies of the action mechanisms of individual circRNAs and the involved regulatory networks are needed.…”
Section: Circrnas Are Promising Biomarkers and Therapeutic Targets Fo...mentioning
confidence: 99%